Indonesia Government Responsiveness during COVID-19 - Kuswandi, Aos; Nuraini, Siti; Dian, Susi; Ramadhina, Khalida Alifia (Journal of Social Politics and Governance (JSPG), 2023)
This article discusses the expansion of the centralization-decentralization dichotomy in the midst of the turbulence of the responsiveness of the Indonesian government by offering an alternative lens of concurrency. Simultaneously centralization and decentralization can be used to respond effectively to crisis events that overlap with administrative jurisdictions and require strong coordination. A qualitative case analysis of the Government of Indonesia’s response to the COVID-19 pandemic, this research finds that concurrency has increased national-subnational tensions which compromised the effective response in the early period of the COVID-19 crisis. This tension is caused by the long-term delay on the part of the central government in the COVID-19 period. This research concludes that concurrency can be effective, but requires a clear division of competencies and consistent implementation from the Government of Indonesia.